Overheating Willingness to Pay: Who Gets Warm Glow and What It Means for Valuation. (August 2014) - Interis, Matthew G.; Haab, Timothy C.
Abstract : In traditional contingent valuation, the researcher seeks the amount a respondent is willing, ceteris paribus, to pay to obtain something. But if a respondent receives a "warm glow" from a yes response, ceteris is not paribus. In estimating willingness to pay (WTP) to reduce environmental impacts from consumption of transportation fuel, we find that respondents who were relatively less environmentally focused in the past receive greater warm-glow benefits from a "yes" response and have greater "warm" WTP (WTP that includes warm-glow benefits). Yet respondents who were relatively more environmentally focused in the past have greater "cold" WTP (WTP excluding warm-glow benefits).